Analisis Efektivitas Strategi Sistem Jemput Bola dalam Meningkatkan Jumlah Nasabah Pada BMT Maslahah Cabang Pembantu Condong - Nasrifah, Maula; Abdel Karim, Ahmed (universitas Islam Zainul Hasan Genggong, 2024)
The ball pick-up system is carried out to introduce BMT to all levels of society, especially the lower middle class as an effort made by BMT to introduce BMT so that people are interested in becoming members by visiting each member's home. The purpose of this study is to determine the effectiveness of the ball pick-up system strategy at BMT Maslahah Condong Sub-Branch in increasing the number of customers and to find out the constraints of the ball pick-up system strategy. This research uses qualitative methods based on the philosophy of postpositivism. Data collection techniques with observation, interviews and documentation. Descriptive analysis techniques by examining and describing the findings that have been obtained from observations and existing documentation. The results of this study indicate that the ball pick-up system is very effective in increasing the number of customers. The effectiveness in question is with active planning and time, integration of communication and work enthusiasm by the BMT. The ball pick-up strategy at BMT has the advantage of providing convenience to customers in transacting with no need to come to the office for transactions, increasing socialisation, providing calendars, delivery and courteous service to members. The obstacles faced are mobile printers that sometimes err, the amount of savings that are not the same amount, and the limited time and lack of employees who run.